Odonata assemblages in highland hydrosystems of northeastern Algeria, with notes on elevational patterns: application of species occupancy models - Ali Elafri; Ismahan Halassi; Abdelah Aoues; Hanin Ghomrassi (Journal of Insect Biodiversity and Systematics)
We aim in this study to increase our knowledge of the Odonata in the Aures, an unexplored region of northeastern Algeria, using single-species occupancy model (spOccupancy R package) coupled with spatial interpolation technique (kriging ArcGis) to assess the relationships between elevation and odonatan species distribution. From time windows of about 90 days (June to August 2021), a total of 22 odonatan species belonging to 2 suborders (Anisoptera and Zygoptera) have been recorded in 15 sampling wet biotopes; among them the endangered Calopteryx exul. Our modelling shows that 62% of the odonatological community has a uniform probability of being present in the studied area. The probability of detecting a species is similar during each survey for 90% of the odonatological community except for the endangered Calopteryx exul (p ˂ 0.05) and Crocothemis erythraea (p ˂ 0.05). We also found that Ischnura graellsii and I. saharensis are the most common species; they are predicted to occur in more than 60% of sites, followed by Anax imperator, Orthetrum chrysostigma, and Platycnemis subdilatata, where they occur in about 50% of the wet biotopes sampled. Finally, our modelling revealed no evidence for a significant altitudinal variation (500 to 1900 meters above sea level) impact on both occupancy and detectability of the majority of the odonatan species, except for Crocothemis erythraea and Sympetrum fonscolombii. The kriging interpolation indicates that they are concentrated within the altitude range of 400 m to 1000 m.